A pre-treatment quality assurance survey on 384 patients treated with helical intensity-modulated radiotherapy. Issue 3 (March 2016) - Bresciani, Sara; Miranti, Anna; Di Dia, Amalia; Maggio, Angelo; Bracco, Christian; Poli, Matteo; Di Spirito, Davide; Gabriele, Pietro; Stasi, Michele
Abstract: The gamma index pass rate (%GP) of 384 helical Tomotherapy pre-patient quality assurance, acquired with ArcCHECK™, is presented, analyzed, and correlated to plan characteristics. Average %GP was higher than 90% and correlated strongly with gamma method, irradiated length, pitch, maximum dose to diodes, and dose per fraction.